2021
DOI: 10.3389/fonc.2021.710191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Systemic Inflammation and Nutritional Indicators in Predicting Recurrence-Free Survival After Surgical Resection of Gastrointestinal Stromal Tumors

Abstract: BackgroundRecent studies have shown that the systemic inflammation and nutritional indicators are prognostic for a variety of malignancies. However, only limited data have so far demonstrated their usefulness in gastrointestinal mesenchymal tumors (GIST).MethodsWe retrospectively analyzed the data of GIST patients who underwent radical surgery in Beijing hospital from October 2004 to July 2018. The area under the receiver operating characteristic curve (AUC) was used to compare several commonly used inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, Elif Yuce et al [ 43 ] found that PNI was not a risk factor for the prognosis of GIST patients. Furthermore, As Dolan et al [ 44 ] published a retrospective analysis including 160 patients who underwent GIST surgery, the authors demonstrated that SII could be used as a prognostic predictor. Similar results were obtained in another retrospective analysis that included 45 GIST patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Elif Yuce et al [ 43 ] found that PNI was not a risk factor for the prognosis of GIST patients. Furthermore, As Dolan et al [ 44 ] published a retrospective analysis including 160 patients who underwent GIST surgery, the authors demonstrated that SII could be used as a prognostic predictor. Similar results were obtained in another retrospective analysis that included 45 GIST patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…SII is calculated by multiplying platelet and NLR and also increases in cases of increased in ammation 21 . Various studies in the literature propose that SII may be used to determine prognosis in patients with malignant disease [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%